On the robustness of DCT-based compression algorithms for space applications - Avramenko, S.; Reorda, M. Sonza; Violante, M.; Fey, G.; Mess, J.-G; Schmidt, R. (Proceedings / IEEE International On-Line Testing Symposium, 2016)
High compression ratio is crucial to cope with the large amounts of data produced by telemetry sensors and the limited transmission bandwidth typical of space applications. A new generation of telemetry units is under development, based on Commercial Off-The-Shelf (COTS) components that may be subject to misbehaviors due to radiation-induced soft errors. The purpose of this paper is to study the impact of soft errors on different configurations of a discrete cosine transform (DCT)-based compression algorithm. This work's main contribution lies in providing some design guidelines.